Assessing PM10 Transmission Changes under Different Lockdown Phases. A Case Study of the City of Colombo - Jayathilaka, H.B.T.P. (Department of Geography, University of Colombo, 2024)
Air pollution is a major man-made disaster, and most researchers have reported that lockdown events such as COVID-19 pandemic are likely to impact air quality. However, there are limited studies in Sri Lanka about spatial and temporal changes in PM10 before, during and after the COVID-19 pandemic. Therefore, this study focused on assessing the spatiotemporal impacts of COVID-19 on PM10 in the Colombo Municipal Council. Landsat 8 (OLI) data and observed PM10 data collected from the NBRO and US embassies in Sri Lanka and Arc GIS 10.5 were used to analyze the PM10 data. The study was conducted in 2019, 2020 and 2021. The year 2020 was identified according to three main phases: Before COVID-19 Lockdown Period, COVID-19 Lockdown Period and the Travel Restriction Period. In 2019 and 2021 were divided according to the 2020 phases, to identify the variations in PM10. According to the results of this study, the accuracy assessment revealed a strong correlation (R2 = 0.89) between the calculated and observed PM10 concentrations. The city of Colombo is highly vulnerable to PM10, and the TRP concentration in 2019 was reported to be high, at 182.33 µg/m3. The lowest PM10 concentration was 20.03 µg/m3, which was reported for LP in 2020. Most areas exceeded the World Health Organization standard value of 50 µg/m3 for PM10 during these three years. The highest PM10 concentrations can be found in port city area, city center, trade center (Fort), road junctions, industrial zones, construction areas, etc. Therefore, it is necessary to take necessary actions to reduce this man-made disaster to create a healthy environment for urban inhabitants.
Keywords: Air pollution; COVID-19; PM10; Landsat; GIS